Effect of Intravenous Magnesium Sulfate on Postoperative Opioid Consumption : An Update Systematic Review of Randomized Controlled Trial - I Gede Agus Rastika; I Komang Adi Kusuma Jaya; I Komang Budi Lastiawan (International Medical Journal Corp. Ltd, 2026)
Introduction: Postoperative pain management frequently relies on opioids, which are associated with significant adverse effects including nausea, vomiting, respiratory depression, and potential for dependence. Intravenous magnesium sulfate, an N-methyl-D-aspartate (NMDA) receptor antagonist, has emerged as a potential non-opioid analgesic adjuvant. This systematic review synthesizes evidence from the last five years on the effect of perioperative intravenous magnesium sulfate on postoperative opioid consumption. Methods: A systematic review of randomized controlled trials (RCTs) published between 2021 and 2025 was conducted. Databases were screened for studies involving adult patients (≥18 years) undergoing surgical procedures, where intravenous magnesium sulfate was administered perioperatively compared to placebo, standard care, or active comparators. The primary outcome was total postoperative opioid consumption. Secondary outcomes included pain scores, postoperative nausea and vomiting (PONV), and adverse effects. Results: Forty-four RCTs encompassing diverse surgical procedures (spinal, gynecological, bariatric, orthopedic, laparoscopic) were included. The vast majority (over 90%) demonstrated that intravenous magnesium sulfate significantly reduced postoperative opioid consumption by approximately 20-50% within the first 24 hours. The most effective regimen was a loading dose of 30-50 mg/kg followed by a maintenance infusion of 10-15 mg/kg/h. Pain scores were significantly reduced primarily in the early postoperative period (0-12 hours). The opioid-sparing effect was most pronounced in procedures with moderate-to-severe baseline pain. One study reported paradoxical increased rescue analgesia using a fixed 3g dose without maintenance infusion. The highest maintenance dose (20 mg/kg/h) caused unacceptable hypotension and bradycardia, establishing 15 mg/kg/h as the upper safe limit. No respiratory depression attributable to magnesium was reported. Discussion: The opioid-sparing effect of magnesium is mechanistically explained by NMDA receptor antagonism, preventing central sensitization and opioid tolerance. The effect size varies with surgical context, baseline multimodal analgesia, and dosing regimen. Weight-based dosing with continuous infusion appears superior to fixed single boluses. The benefit attenuates by 48 hours, suggesting prolonged infusion may extend analgesia. The safety profile is favorable at standard doses. Conclusion: Intravenous magnesium sulfate at doses of 30-50 mg/kg loading and 10-15 mg/kg/h maintenance consistently reduces postoperative opioid consumption by 20-50% with a favorable safety profile. It is most beneficial in surgeries with expected moderate-to-severe pain and should be considered part of multimodal analgesia, particularly when minimizing opioid exposure is desirable.